1999
DOI: 10.1093/intimm/11.7.1043
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of peptide vaccine protects human/mouse radiation chimera from influenza infection

Abstract: Influenza virus is characterized by frequent and unpredictable changes of the surface glycoproteins which enable the virus to escape the immune system. Approved vaccines which consist of the whole virus or the surface glycoproteins fail to induce broad specificity protection. We have previously reported that a peptide-based experimental recombinant vaccine which includes conserved epitopes of B and T lymphocytes was efficient in mice, leading to cross-strain, long-term protection. In the present study, this ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 53 publications
2
38
0
1
Order By: Relevance
“…The transplanted mice that were immunized with the recombinant flagella also lost weight as a result of the infection, but they recovered rapidly and as mentioned, 100% survival was monitored in this group. 65 These results emphasize the high efficacy of the tetra vaccine in the humanized mice and its potential for the development of a vaccine for human use. A start-up company has been established aiming at the development of such vaccine and its evaluation in clinical trials.…”
Section: Towards a Human Influenza Vaccinementioning
confidence: 82%
“…The transplanted mice that were immunized with the recombinant flagella also lost weight as a result of the infection, but they recovered rapidly and as mentioned, 100% survival was monitored in this group. 65 These results emphasize the high efficacy of the tetra vaccine in the humanized mice and its potential for the development of a vaccine for human use. A start-up company has been established aiming at the development of such vaccine and its evaluation in clinical trials.…”
Section: Towards a Human Influenza Vaccinementioning
confidence: 82%
“…Intranasal immunization has been used before both in laboratory mouse models (24,50,51) and in domestic animal species (52), while bacterial components have also been used successfully in immunization (21,22,53,54), but the combination of these methods for nematode vaccination has not been tested except in a recent experiment using the same protein, PP2Ar, against A. costaricensis (20) in mice. Immunization provoked lower parasite burdens and increased levels of interleukin-17 (IL-17) and specific IgA.…”
Section: Resultsmentioning
confidence: 99%
“…Arnon et al demonstrated that recombinant flagellin containing foreign epitopes caused protective immune responses in the absence of any additional adjuvant, flagellin has effects on T cells proliferation and cytokine responses (24,25). The induction of potent cell-mediated immunity will be necessary and may require the induction of cytotoxic T cell (CTL) which kills host cells infected with intracellular pathogens (12).…”
Section: Discussionmentioning
confidence: 99%